2014
DOI: 10.1103/physrevb.90.195441
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Mn-acceptor state and Dirac surface states in Mn-dopedBi2Se3topological insulator

Abstract: We investigate the properties of a single substitutional Mn impurity and its associated acceptor state on the (111) surface of Bi 2 Se 3 topological insulator. Combining ab initio calculations with microscopic tight-binding modeling, we identify the effects of inversion symmetry and time-reversal-symmetry breaking on the electronic states in the vicinity of the Dirac point. In agreement with experiments, we find evidence that the Mn ion is in the +2 valence state and introduces an acceptor in the bulk band gap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Obviously, the bias dependence of the transition rate provides a route to electrically control P M and in turn the self-energy in Eq. (7).…”
Section: Electrical Manipulation Of Dprmentioning
confidence: 95%
See 3 more Smart Citations
“…Obviously, the bias dependence of the transition rate provides a route to electrically control P M and in turn the self-energy in Eq. (7).…”
Section: Electrical Manipulation Of Dprmentioning
confidence: 95%
“…2 (c), increases, which significantly modifies the self-energy (ω) in Eq. (7). At the same time, the nanomagnet is polarized as shown in Fig.…”
Section: Electrical Manipulation Of Dprmentioning
confidence: 97%
See 2 more Smart Citations
“…Experiments1820 and theoretical calculations2930 have suggested that the magnetic dopants, such as V, Cr, Mn and Fe, will mostly substitute the Bi or Sb ions in 3D TIs; we therefore concentrate on this situation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%